PREPARATION AND ASSESSMENT OF NAIL LACQUER INCORPORATING CICLOPIROX OLAMINE-LOADED NIOSOMES - AYUSHI CHAUHAN; MANSI BUTOLA; VIKASH JAKHMOLA; JYOTI MAITHANI KALRA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The emergence of transungual drug delivery systems represents a significant advancement in treating nail-related conditions, particularly fungal infections like onychomycosis. The current study aims to formulate ciclopirox olamine (CPO)-loaded niosomal nail lacquer for the treatment of onychomycosis. Methods: CPO niosomes were synthesized using the thin-film hydration method, incorporating different proportions of cholesterol, Span 60, and Tween 40. Niosomes were assessed for their drug content, encapsulation efficiency, particle size, and zeta potential. Results: Among various formulations of niosomes, the formulation F5 showed adequate drug loading of 94.51%, polydispersity index of 0.171, and zeta potential of −5.10 mV. Following that, the optimized formulation (F5) of the niosomal suspension was used to develop nail lacquer formulation. The optimized nail lacquer formulation (F5) showed the maximum in vitro drug release, achieving a rate of 92.22%. The ex vivo transungual study of the optimized formulation was conducted using Franz diffusion cell apparatus, resulting in a drug release rate of approximately 90.67%. The zone of inhibition obtained for niosomal nail lacquer formulation was found more than the pure drug solution. Conclusion: The oral administration of antifungal agents, such as allylamines and azoles, is associated with numerous adverse effects resulting from the requirement for high dosages. These issues can be addressed by formulating such medications as nail lacquer, using significantly lower dosages for treatment, which consequently leads to reduced side effects